A comparative study of open haemorrhoidectomy and stapled haemorrhoidopexy in grade 3 and 4 haemorrhoids - Bagul, Abhijit G.; Oak, Aditya C.; Shah, Yashraj (International Surgery Journal, 2026)
Background: Haemorrhoids are a common anorectal condition seen in surgical practice. Open haemorrhoidectomy described by Milligan Morgan is a widely used procedure. According to Dr. Antonio Longo, basic pathology of haemorrhoidal disease is prolapse above the haemorrhoidal tissue. He proposed correction of prolapse by resecting the prolapsed suprahaemorrhoidal rectal mucosa using stapler popularly known as stapled haemorrhoidopexy. We aim to compare stapled haemorrhoidopexy with open haemorrhoidectomy in the management of grade 3 and grade 4 haemorrhoids. Methods: Fifty patients with grade 3 or grade 4 haemorrhoids were included in the study. The 25 patients underwent open haemorrhoidectomy and 25 underwent stapled haemorrhoidopexy. Patients were followed up on day 7, day 15, 1 month, 3 months, 6 months and 1 year for any complications encountered. The two groups were compared for duration of surgery, duration of hospital stay, postoperative pain, postoperative bleeding, urinary retention, anal incontinence, postoperative infection and return to work. Results: In our study, mean age was 44 years, majority of patients were males and had grade 3 haemorrhoids. Stapled haemorrhoidopexy group had shorter duration of surgery and hospital stay, less postoperative pain, earlier return to work and good patient compliance. In the follow up period there was no postoperative bleeding, no postoperative infection, recurrence, residual prolapse or incontinence in the stapled group. Conclusions: Stapled haemorrhoidopexy is superior and a safe alternative to open haemorrhoidectomy in management of grade 3 or grade 4 haemorrhoids.